Bounce Balloon Enterprise : Bounce Balloon / Muhammad Amirulfikri Suhaimi ... [et al.] - Suhaimi, Muhammad Amirulfikri (2017)
For your information, the main idea of our business is the important of love between human being and enjoyable outdoor activities that guarantee can improve happiness of human being without gadget. As we known gadget control our live activities nowadays, so we made our business with trading and services of bounce balloon that we can use in Malaysia which has the most cheaply outdoor activities. Our services conclude 3 types of bounce balloon which is party bounce balloon, small bonce balloon and inflatable bounce balloon. Each of them has different and challenging games that can attract all Malaysian to get a try. Through our long term of observation and research, almost all theme park in Malaysia are so expensive and has the same games but our inflatable balloon are the new games that play at the east beach of Malaysia.